PUTINISM AND ITS IDEOLOGICAL BACKGROUND AS A PROBLEM OF MODERN THEORETICAL DISCOURSE IN SOCIAL SCIENCIES AND HUMANITIES - Grabovska, Iryna; Tetyana, Talko (Київський національний університет імені Тараса Шевченка, 2019)
The article explores the problem of the ideology of Putinism. It draws attention to the fact that in modern analytical texts about the phenomenon of Putinism, the dispute between scholars has shifted toward clarifying its ideological foundations. A few years ago, an intense scientific debate about the correctness of usage of the term "Putinism" itself took place. The authors investigate the current analytical publications on the ideological foundations of Putinism. The article points out the divergence of views of researchers on the existence of state ideological doctrine developed in the current Kremlin regime. The purpose of this article is defined as proving the fact that Putinism is not only a practical but also an ideological phenomenon of our age. The authors conclude that the ideology of Putinism exists. It seems convincing to consider Putinism as an ideological doctrine of the hybrid type, the general characteristic of which can be defined as neo-imperialism of the autocratic type with the elements of totalitarianism, "assembled" from a set of different doctrines of the past and present. Among them: Pan-Slavism, Russo-Centrism, Eurasianism and Neo-Eurasianism, Duginism (ideologically extremely close to the ideology of the Third Reich and the ideologists of the German "conservative revolution" at the same time, according to L. Lux), Messianism, Isolationism, Anti-Westernism and Anti-Americanism, Neo-Stalinism, Orthodox Fundamentalism, the role of the strong leader. Putinism as a neo-imperialist ideology is in line with the Kremlin's practice, beginning with Putin's rise to power when neo-colonial wars began on the perimeter of the former Soviet empire. It is partly orientated to suppress internal separatist movements, as it was in the case of Chechnya and partly to attempts to "gathering lands" as in the case of Georgia and now – of Ukraine.

Досліджується зміст ідеології путінізму. Акцентується увага на тому факті, що у сучасних аналітичних текстах, присвячених явищу путінізму, суперечка між науковцями змістилася у бік з’ясування його ідеологічних засад. Ще декілька років тому велися гострі наукові дискусії про можливість вживання самого терміну «путінізм». Проведено аналіз актуальних аналітичних публікацій із питання ідеологічних засад путінізму. Вказано на розбіжності у поглядах дослідників щодо наявності у сучасного режиму Кремля виробленої державної ідеологічної доктрини. Визначено мету даної статті як доведення того факту, що путінізм є не лише практичним, але й ідеологічним феноменом нашої доби. Робиться висновок щодо наявності ідеології путінізму. Видається переконливим вважати путінізм ідеологічною доктриною гібридного типу, загальна характеристика якої може бути визначена як неоімперіалізм автократичного типу з елементами тоталітаризму, базований, «зібраний» із сукупності різних доктрин минулого та сучасності. Серед них: панславізм, росієцентризм, євразійство та неоєвразійство, дугінізм (ідейно надзвичайно близький ідеології Третього Рейху та ідеологів німецької «консервативної революції» водночас, на думку Л. Люкса), ізоляціонізм, антизахідництво та антиамериканізм, неосталінізм, месіанство, православний фундаменталізм, вождизм тощо. Визначення ідеології путінізму як неоімперіалізму відповідає його практиці, починаючи від середини 2000-х, коли розпочалися неоколоніальні війни по периметру колишньої Совєтської імперії, частково з метою придушення внутрішніх сепаратистських рухів, як то було із Чечнею, частково із прагненням «собирания земель» у випадку із Грузією та нині – з Україною.
ПУТІНІЗМ ТА ЙОГО ІДЕОЛОГІЧНІ ЗАСАДИ ЯК ПРОБЛЕМА СУЧАСНОГО ТЕОРЕТИЧНОГО ДИСКУРСУ В СОЦІОГУМАНІТАРИСТИЦІ
Keywords: Ukraine; Russia; Putinism; ideology; Neo-Imperialism; Revanchism; pragmatism; Messianism; Україна; Росія; путінізм; ідеологія; неоімперіалізм; реваншизм; прагматизм; месіанізм